Definitions and methods of formation of usual expressions in Chinese language - Койбaковa, A. С. (Journal of Oriental Studies, 2017)
Definitions (惯用语) or steady combinations in Chinese language are stabled spoken rales which are used daily among people. Nowadays, this kind of definitions are build by usual oral norms. They are used not only in conversation, but also in publistic and different types of artistic literatures. This article focuses in definitions in Chinese language which will be learned. And also how are made some of steady combinations of words.